(untitled) (قضايا سياسية, 2022)
That all human societies seek to build their societies in a way that meets the needs of the people of society and live in peace and security, but the endeavor to achieve this in Iraq faces several obstacles whose sources range from internal and external constraints reflected on society in all its aspects, as the Iraqi society passed after 2003 Harsh conditions and challenges have caused a tremendous decline in the indicators of human security in all its economic, food, health, environmental, personal, political and social dimensions, as Iraqi society faced a major threat to human security, especially as the threat targeted the destruction of economic, social and cultural infrastructure and segmentation of society And spreading a state of chaos and insecurity in it, which was clearly reflected in several categories, perhaps the most important of them: women, childhood, youth, people with special needs and displaced people, in addition to the high rates of poverty and unemployment, and the retreat of the health and education system, all of these changes led to creating an environment of Human insecurity.